Os cavaleiros do Graal e o anti-heroísmo hagiográfico - Ana Margarida Chora (Medievalista)
Medieval Arthurian heroes who, in the Vulgate and Post-Vulgate texts, are destined to the Grail adventure (Lancelot, Boorz, Perceval and Galaad) follow a very similar pathway to those of saints narratives of the same period, which goes through predestination and change of behaviour, from a certain moment, taking them to spiritual life. But if, on the one hand, their heroic characteristics determine the specificity of their ascetic evolution; on the other, hagiographic pathways in medieval narratives have forms that touch anti-heroism.